2020
DOI: 10.16984/saufenbilder.545929
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of exopolysaccharide production of Lactobacillus brevis E25 using RSM and characterization

Abstract: Response surface methodology was used to determine the exopolysaccharide production of Lactobacillus brevis E25. The effects of three variables, temperature (30, 36 and 42 °C), incubation time (18, 33 and 48 h) and initial pH of growth medium (4.5, 5.5, and 6.5) were studied. Under optimum growth conditions, the amount of exopolysaccharide derived from Lactobacillus brevis E25 ranged from 10 to 35 gL-1. The size of EPS molecules ranged from 10 5 to 10 7 Da. Infra red spectrum analysis showed characteristics ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, in Whey and Whey-l, the EPS yields were significantly higher than in MRS-1, confirming that lactose had a positive influence on EPS production. While studies on EPS production with this strain are limited, Ermiş et al [64] observed much higher production values for L. brevis E25, which produced from 10 to 35 g/L in MRS broth.…”
Section: Discussionmentioning
confidence: 77%
“…However, in Whey and Whey-l, the EPS yields were significantly higher than in MRS-1, confirming that lactose had a positive influence on EPS production. While studies on EPS production with this strain are limited, Ermiş et al [64] observed much higher production values for L. brevis E25, which produced from 10 to 35 g/L in MRS broth.…”
Section: Discussionmentioning
confidence: 77%
“…The FT-IR spectrum of the EPS was determined in the range of 400–4000 cm −1 using an FT-IR spectrometer (Thermo-scientific type, model Nicolet—IS 10, USA) 47 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent evidence suggests that exopolysaccharide produced by various LAB strains is involved in potential biological activities, such as antioxidant and antibacterial properties [3,15,25,28]. Therefore, as the demand for natural polymers gradually increases in various industrial fields, research on exopolysaccharide produced by microorganisms has been conducted in recent years [1,2,9]. Many microorganisms can synthesize exopolysaccharide and excrete it out of the cell [8].…”
Section: Introductionmentioning
confidence: 99%